The idiomatic significance of the “Daun yang jatuh tak pernah membenci angin” novel by Tere Liye - Maguna Eliastuti (Universitas Indraprasta PGRI, 2017)
The purpose of this study was to determine the meaning Idiomatical forms that exist in the Fall Leaves novel Daun Yang Jatuh Tak Pernah Membenci Angin Tere Liye work, in addition to determine the effect of Use idiomatical meaning of the novel Daun Yang Jatuh Tak Pernah Membenci Angin by Tere Liye. The method used to analyze the novel is the method of observation (observation). Moreover, the authors used a qualitative approach in preparing their work. After analyzing the novel's author analyze the novel The Falling Leaves Never Hate Wind Tere Liye works by analyzing the meaning of idiomatical, finally the author can draw the conclusion that there are two types of idiomatical emerging that idiom partial and full idiom.